MIMPI SYEKH AHMAD MAKAR NASKAH MELAYU KAMPAR: KAJIAN FILOLOGI - Devi Fauziyah Marifat (Balai Bahasa Provinsi Riau, 2015)
The manuscript is a cultural heritage of a past history of a community in the form of handwriting. Reviewing the manuscript could be an interesting matter, especially as a handwriting that has kept various expressions of culture and thought of past culture heritage, and it contains historical elements. As a concrete object, a script is the object of a research for various fields of science, among others: philology, history, archaeology, codicology, and paleography. Each codex contains cultural values, but its form does not appear explicitly, so in order to recognize, it is necessary to carry out a gradual and accurate research. Hence, it is necessary to understand and to recognize seriously the concept of cultural value. The goal is that the concept is not only known as an understanding, but also can be used as guidelines to understand the culture of the people in the past. The purpose of this research is to create a critical issue that can be understood by a wider audience and present the themes contained in the manuscript of Mimpi Syekh Ahmad Makar. It is hoped that the readers can take the wisdom or philosophy contained in the manuscript.